THE EFFECT OF WHISTLEBLOWING, HUMAN RESOURCE COMPETENCE AND INTERNAL CONTROL SYSTEM ON FRAUD PREVENTION OF PSR FUNDS - Andini Syafitri; Dian Puji Puspita Sari; Agustiawan Agustiawan (JASS (Journal of Accounting for Sustainable Society), 2023)
PSR supports smallholders in transforming their oil palm plantations by producing more sustainable and high-quality palm oils, which reduces the risk of illegal land reclamation. This is known as Peremajaan Sawit Rakyat (PSR). To prevent the fraud/fraud of PSR funds, BPDKS distributes funds through escrow accounts of plantation organizations. This is for transaction security. Furthermore, as part of the implementation of PSR, BPK and Sucofindo were audited as BPDPKS designated entities. Fraud prevention can be influenced by a number of factors such as whistleblowing, human resource capacity and internal control systems. Whistleblowing is the disclosure of illegal, unethical, immoral, or other conduct that may cause damage to the organization and its stakeholders. The purpose of this study is to: Determine the impact of whistleblowing on fraud prevention, how human resource skills and internal control systems influence fraud prevention. Research variables (whistleblowing, human resource capacity and internal control system) with a total of 52 samples. Descriptive statistical analysis was used to determine the trend of each research variable. The average scores for whistleblowing, human resource capacity and internal control system are 32.46, 26. 96 and 63.77. The average fraud prevention score is 41.25. Based on the research results, it can be concluded that whistleblowing, human resource capacity and 3. Internal control system affects the prevention of fraud of PSR funds.